2023
DOI: 10.1002/hep.32772
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel neutralizing determinants for protection against HCV

Abstract: Background and Aims: HCV evasion of neutralizing antibodies (nAb) results in viral persistence and poses challenges to the development of an urgently needed vaccine. N-linked glycosylation of viral envelope proteins is a key mechanism for such evasion. To facilitate rational vaccine design, we aimed to identify determinants of protection of conserved neutralizing epitopes. Approach and Results: Using a reverse evolutionary approach, we passaged genotype 1a, 1b, 2a, 3a, and 4a HCV with envelope proteins (E1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The other possibility is that the N417S change affects the global E1E2 conformation by limiting the accessibility of epitope I to AP33-like antibodies. In line with this hypothesis, previous studies have shown that amino acid changes within the 412–423 epitope or in the adjacent regions can result in global conformational changes in the HCV envelope heterodimer ( 38 , 39 ). Similarly, global E1E2 conformation shifts were observed for HCVcc with selected N-glycans removed, resulting in neutralization sensitivity changes that could not simply be explained by the “glycan shield” model ( 40 ).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The other possibility is that the N417S change affects the global E1E2 conformation by limiting the accessibility of epitope I to AP33-like antibodies. In line with this hypothesis, previous studies have shown that amino acid changes within the 412–423 epitope or in the adjacent regions can result in global conformational changes in the HCV envelope heterodimer ( 38 , 39 ). Similarly, global E1E2 conformation shifts were observed for HCVcc with selected N-glycans removed, resulting in neutralization sensitivity changes that could not simply be explained by the “glycan shield” model ( 40 ).…”
Section: Discussionmentioning
confidence: 59%
“…JFH1-based HCV recombinants with core-NS2 of the following genotypes (isolates) and the specified cell culture-adaptive changes were used: 1a (H77) with V787A and Q1247L (H77:WT) ( 51 ), 1a (H77) with the N417S change (H77:N417S) ( 39 ), 5a (SA13) with A1022G and K1119R (SA13:WT) ( 52 ), and 6a (HK6a) with F350S and N417T (HK6a:N417T) ( 53 ). HCVcc stocks were produced in Huh7.5 cells as described previously ( 53 ), and the envelope protein sequences were confirmed by Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Here, N417 is an important glycosylation site in the glycoprotein E2, shielding the virus from neutralizing antibodies [55]. Mutational changes at amino acid position 417 are often found in viruses adapted to cell culture due to absence of selection pressure exerted by neutralizing antibodies [56, 57]. Increased exposure of neutralizing epitopes was previously reported to correlate with an increase in viral fitness likely due to increased accessibility of the CD81 binding site [57].…”
Section: Discussionmentioning
confidence: 99%
“…Mutational changes at amino acid position 417 are often found in viruses adapted to cell culture due to absence of selection pressure exerted by neutralizing antibodies [56, 57]. Increased exposure of neutralizing epitopes was previously reported to correlate with an increase in viral fitness likely due to increased accessibility of the CD81 binding site [57]. However, neither p100pop nor the p100 molecular clone, both harboring an adaptive coding mutation at position 417 (Table 1), showed an altered sensitivity to blocking of the HCV receptor CD81 compared to Jc1 (Fig.…”
Section: Discussionmentioning
confidence: 99%